(untitled) (Global Journal of Management and Business Research, 2012)
All over the world there are two sources that influence consumer buying behavior. The first is formal source, which is a kind of source which is well planned and paid for example advertising, personal selling, sale promotion and public relation. The second source is informal which is a kind of source which is not pre planned and non paid like reference group, culture etc. This research emphasizes that how formal and informal sources affect consumer buying behavior. For the research a sample of 200 students of three private universities targeted from Peshawar region. On the basis of their responses a regression and correlation analysis was conducted. Findings and results of the study shows that formal sources have more influence on consumer buying behavior. Within the formal sources advertising is the key factor which contributes more towards consumer buying behavior for telecom services. While in case of informal sources reference group contribute more in comparison of other informal sources towards consumer buying behavior for telecom services.